Blind adolescents' birth order as a determinant of their perception of family functioning dimensions - Stanimirović Dragana (Specijalna Edukacija i Rehabilitacija, 2013)
While other theoreticians of personality stressed only the influence of parents in early childhood, Adler paid particular attention to a psychological position of a child among brothers/sisters. There is some empirical evidence that birth order may influence vocational choice, characteristic style of interacting with others, affiliation, anxiety, perception of parents' authority, and even intellectual capabilities. Visual impairment of a family member affects a family system and a sibling subsystem in a specific way. The goal of the research was to determine whether birth order influences perception of dimensions of family functioning in families with a blind adolescent and in families with an adolescent of typical development. The sample included 32 blind (experimental group) and 32 subjects of typical development (control group) aged 14 to 26, who lived in complete families with two or three children and without serious personal, marrital or family problems. The groups were paired by sex, age, professional status and birth order of adolescents, number of children in the family, type of family (nuclear; extended) and environment (rural; urban). A Questionnaire of socio-demographic information and a Questionnaire of situation and family relationships RADIR by Knežević were applied for data collection. First-borns made lower appraisals of each dimension of family functioning than second-born respondents. There were no statistically significant differences in the control group. Differences in the experimental group were statistically significant in the following dimensions: Activity, Democracy and Structuring time and activity. Thus, the results show that first-born child's 'dethronement' has more effect if it is associated with blindness. This can be explained by fact that it is more difficult for a blind first-born child to catch up with a second-born 'rival'.